2010
DOI: 10.2147/cpaa.s12126
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic efficacy of oral gabapentin added to standard epidural corticosteroids in patients with failed back surgery

Abstract: ObjectiveFailed back surgery syndrome is characterized by the presence of intractable pain and varying degrees of functional incapacity after lumbar spine surgery. Because the mechanisms that cause pain are variable, treatment of this syndrome is quite difficult, and one of the most common methods that is used for treatment nowadays is epidural injection. This research evaluates the analgesic efficacy of addition of oral gabapentin treatment to epidural corticosteroid application in patients with failed back s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 37 publications
(36 reference statements)
0
19
0
1
Order By: Relevance
“…Zencirci et al54 demonstrated that adding Gabapentin to ESI in patients with FBSS from at least two prior surgeries for lumbar disc herniation had significantly lower pain levels at 1 and 3 months compared with those who received ESI while taking naproxen sodium, tizanidine, and vitamin B and C complex 54. This study underlies the importance of a multimodal approach to treating FBSS.…”
Section: Management Of Fbssmentioning
confidence: 74%
“…Zencirci et al54 demonstrated that adding Gabapentin to ESI in patients with FBSS from at least two prior surgeries for lumbar disc herniation had significantly lower pain levels at 1 and 3 months compared with those who received ESI while taking naproxen sodium, tizanidine, and vitamin B and C complex 54. This study underlies the importance of a multimodal approach to treating FBSS.…”
Section: Management Of Fbssmentioning
confidence: 74%
“…An 8‐week course of gabapentin was found to be superior to a stellate ganglion block using bupivacaine in a trial involving 60 patients after mastectomy. The addition of 1 month of oral gabapentin to standard epidural corticosteroids was found to result in lower pain at 6 months compared with epidural corticosteroids alone after spinal surgery.…”
Section: Resultsmentioning
confidence: 91%
“…Eight trials including data from 338 participants evaluated the effects of antiepileptic medications on CPSP. The largest number of studies for any one technology was for gabapentin (6 studies, 293 participants with pain after amputation, breast cancer surgery, sternotomy and spinal surgery). Four trials were at risk of bias owing to issues relating to blinding, blinding and randomization, incomplete outcome data, and blinding and single‐authored article.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 FBSS can be defined as persistent or recurring low back pain, with or without sciatica following one or more lumbar surgeries. 35 The rate of the FBSS increased in the last two decades despite of the advances in surgical technology. 14,22 A recent systemic literature review of discectomies for lumbar disc herniation demonstrates that 5%-36% of patients after 2 years had FBSS below the age of 70 years.…”
Section: Introductionmentioning
confidence: 99%